2013
DOI: 10.1007/s00213-013-3134-5
|View full text |Cite|
|
Sign up to set email alerts
|

The role of the cholinergic system in the signal attenuation rat model of obsessive-compulsive disorder

Abstract: Acetylcholine does not seem to play a role in the signal attenuation rat model of OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Evidence exists for cholinergic involvement in OCD (Lucey et al, 1993; Yankelevitch-Yahav and Joel, 2013). Some studies have indicated exacerbation of OCD symptoms induced by nicotine (Abramovitch et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists for cholinergic involvement in OCD (Lucey et al, 1993; Yankelevitch-Yahav and Joel, 2013). Some studies have indicated exacerbation of OCD symptoms induced by nicotine (Abramovitch et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An animal model showed that cholinergic interneurons’ activity in NAC were associated with adaptive cue-motivated behavior, present in many psychiatric conditions [ 39 ]. Acetylcholine seems to not interfere with signal attenuation in the cholinergic system of compulsive behavior in a rat model of OCD [ 40 ]. Nevertheless, in pediatric obsessive-compulsive disorder, specifically in children with PANDAS (Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections), cholinergic interneurons activity in the striatum may contribute to pathophysiology in children with rapid-onset OCD symptoms [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…, and has been extensively used to study the neural substrates of this behavior 39,[43][44][45]48 , its response to pharmacological manipulations 38,39,43,47,53,54 and to deep brain stimulation 40,46,50 and its modulation by ovarian hormones…”
Section: Discussionmentioning
confidence: 99%